Bee chitosan nanoparticles loaded with apitoxin as a novel approach to eradication of common human bacterial, fungal pathogens and treating cancer - Sharaf, Mohamed; Zahra, Abdullah A.; Alharbi, Maha; Mekky, Alsayed E.; Shehata, Abdelrazeq M.; Alkhudhayri, Abdulsalam; Ali, Ahmed M.; Al Suhaimi, Ebtesam A.; Zakai, Shadi A.; Al Harthi, Norah; Liu, Chen-Guang (Frontiers in Microbiology, 2024)
Antimicrobial resistance is one of the largest medical challenges because of the rising frequency of opportunistic human microbial infections across the globe. This study aimed to extract chitosan from the exoskeletons of dead bees and load it with bee venom (commercially available as Apitoxin [Api]). Then, the ionotropic gelation method would be used to form nanoparticles that could be a novel drug-delivery system that might eradicate eight common human pathogens (i.e., two fungal and six bacteria strains). It might also be used to treat the human colon cancer cell line (Caco2 ATCC ATP-37) and human liver cancer cell line (HepG2ATCC HB-8065) cancer cell lines. The x-ray diffraction (XRD), Fourier transform infrared (FTIR), and dynamic light scattering (DLS) properties, ζ-potentials, and surface appearances of the nanoparticles were evaluated by transmission electron microscopy (TEM). FTIR and XRD validated that the Api was successfully encapsulated in the chitosan nanoparticles (ChB NPs). According to the TEM, the ChB NPs and the ChB NPs loaded with Apitoxin (Api@ChB NPs) had a spherical shape and uniform size distribution, with nonaggregation, for an average size of approximately 182 and 274 ± 3.8 nm, respectively, and their Zeta potential values were 37.8 ± 1.2 mV and –10.9 mV, respectively. The Api@ChB NPs had the greatest inhibitory effect against all tested strains compared with the ChB NPs and Api alone. The minimum inhibitory concentrations (MICs) of the Api, ChB NPs, and Api@ChB NPs were evaluated against the offer mentioned colony forming units (CFU/mL), and their lowest MIC values were 30, 25, and 12.5 µg mL–1, respectively, against Enterococcus faecalis. Identifiable morphological features of apoptosis were observed by 3T3 Phototox software after Api@ChB NPs had been used to treat the normal Vero ATCC CCL-81, Caco2 ATCC ATP-37, and HepG2 ATCC HB-8065 cancer cell lines for 24 h. The morphological changes were clear in a concentration-dependent manner, and the ability of the cells was 250 to 500 µg mL–1. These results revealed that Api@ChB NPs may be a promising natural nanotreatment for common human pathogens.